2021
DOI: 10.3390/universe7120496
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Longitudinal Polarizations in Horndeski and Macroscopic Gravity: Introducing Gravitational Plasmas

Abstract: We discuss some general and relevant features of longitudinal gravitational modes in Horndeski gravity and their interaction with matter media. Adopting a gauge-invariant formulation, we clarify how massive scalar and vector fields can induce additional transverse and longitudinal excitations, resulting in breathing, vector, and longitudinal polarizations. We review, then, the interaction of standard gravitational waves with a molecular medium, outlining the emergence of effective massive gravitons, induced by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 169 publications
0
7
0
Order By: Relevance
“…The primordial black holes(PBH) are also studied as viable candidate for dark matter and the detection of GW signal emitted from such sources has been considered earlier [39][40][41][42][43]. In a different context concerning macroscopic gravity, the GW propagation dealing with modified dispersion relation and extra degrees of polarization in extended theories of gravity has been looked into in [44][45][46][47]. In this paper, we rather focus explicitly on DM condensate candidates that serve as constituent candidates for galactic DM halo.…”
Section: Jcap03(2023)041mentioning
confidence: 99%
“…The primordial black holes(PBH) are also studied as viable candidate for dark matter and the detection of GW signal emitted from such sources has been considered earlier [39][40][41][42][43]. In a different context concerning macroscopic gravity, the GW propagation dealing with modified dispersion relation and extra degrees of polarization in extended theories of gravity has been looked into in [44][45][46][47]. In this paper, we rather focus explicitly on DM condensate candidates that serve as constituent candidates for galactic DM halo.…”
Section: Jcap03(2023)041mentioning
confidence: 99%
“…General relativity (GR) predicts that only two tensor polarizations exist for the GW, the plus and cross modes. However, there are additional four polarizations allowed by the generic metric theories of gravity, including two vector modes and two scalar modes (Brans & Dicke 1961;Eardley et al 1973;Jacobson & Mattingly 2004;Sagi 2010;Liang et al 2017a;Moretti et al 2019Moretti et al , 2020Moretti et al , 2021. The observation of vector or scalar modes would cast doubt on general relatively, while their absence could be used to constrain modified gravity (Will 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we speak of velocity birefringence when waves with left and right handed polarizations [59] propagate with different speeds, while in the presence of a different friction term for the two modes we have amplitude birefringence, in which the enhancement or suppression of the wave depends on its chiral state. Furthermore, when propagation within a material medium is also considered, it can be demonstrated that velocity birefringence can generate amplitude birefringence through the Landau damping phenomenon [60], consisting in the kinematic damping of gravitational waves in the absence of collisions (see [61][62][63][64][65][66][67][68][69][70][71][72] for more details). Gravitational wave birefringence is a well-established result of metric CSMG [23,[73][74][75], and in this work we show for the first time how such a phenomenon is present also in the metric-affine formulation.…”
Section: Introductionmentioning
confidence: 99%